2016
DOI: 10.19104/crcm.2016.116
|View full text |Cite
|
Sign up to set email alerts
|

Ketoacidosis Related to Infections Induced by Bee Sting: A Case Report

Abstract: Diabetic ketoacidosis is a life-threatening complication of diabetes, and its mortality increasing with age is about 5 %. Infectious diseases are the most prevalent causes of diabetic ketoacidosis. Indeed, infections related to bee sting are unusual. However, even if it's not frequent, cases with infection have been reported. In this report, we aimed to present a diabetic ketoacidosis case associated with bee sting in a patient with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The third is the tendency of infection due to a damaged epidermis resulting from scratching of the sting site. 2 There are reports of septicemia occurring after insect stings, caused by pathogens entering the human body via the pores when stingers are left embedded in the skin. 4 In some research, the culture specimen from insect sting lesion revealed Staphylococcus aureus, Pseudomonas aeruginosa, Enterococcus faecalis, Xanthomonas maltophila, and coagulasenegative Staphylococcus species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third is the tendency of infection due to a damaged epidermis resulting from scratching of the sting site. 2 There are reports of septicemia occurring after insect stings, caused by pathogens entering the human body via the pores when stingers are left embedded in the skin. 4 In some research, the culture specimen from insect sting lesion revealed Staphylococcus aureus, Pseudomonas aeruginosa, Enterococcus faecalis, Xanthomonas maltophila, and coagulasenegative Staphylococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…The venom has substances and enzymes such as hyaluronidase, phospholipase A2, and Melittin, which can destroy the cell membrane, degranulate mast cells, and release immunoglobulin E (IgE), resulting in inflammation and allergic reactions. 2 The venom enters the tissue through sting or bite. Insect sting can lead to local reactions like pain, redness, swelling, and even allergic reaction.…”
Section: Introductionmentioning
confidence: 99%